Evaluación del bosque de colina baja de la concesión Negociaciones Yacory EIRL. Para el aprovechamiento sostenido, río Tacsha Curaray - Loreto, Perú - 2021 - Valles Del Aguila, Alen Jhunior (2022)
The study was developed in the low hill forests of the Negociaciones Yacory EIRL concession, for sustained use, Tacsha Curaray Loreto River, Peru. The objectives were to record the floristic composition of commercial species with diameter 40 cm; determine the IVI; define the volume of standing commercial timber and the economic valuation. The population. The study area was in total (ha): 6,407,255 of the forests of the Negociaciones Yacory EIRL concession. The sample was 702,823 (ha). The methodology used to do the field work was the design of a random inventory. 46 commercial species were found, distributed in 20 botanical families. The largest number of species is in the botanical family Fabaceae, Vochysiaceae. The abundance of commercial species is in the Fabaceae family, which represents 30.37 of the total number of species registered in the forest inventory of the study area; The dominance of commercial species is 17421852.76 m2 / ha. The most frequent species are "Quillosisa, Pashaco, Tangarana". The representative species, according to the IVI are, "Quillosisa, Tangarana, Pashaco, Aluje rumo, Cumala, Caimitillo, Machimango, Palisangre, Cumala llorona, Vidrio". The volume of commercial wood is 25.27 m3 / ha. The species with the highest Valorization per hectare is the Quillosisa with S/. 333.88 soles.